Intervensi Akupresur untuk Neuropati Perifer pada Diabetes Melitus dengan Sindrom Lembab Limpa: Studi Kasis dan Literatur Review - Ni Ketut Sujati; M Agung Akbar; Hesti Anggraeni; Laila Fadhillah (Universitas Faletehan, 2024)
Spleen dampness syndrome (Pi Xu Re Yang) characterized by impaired circulation and fluid metabolism exacerbates complications of peripheral neuropathy, peripheral artery disease, and infection in diabetic patients that can lead to limb amputation. The development of diabetic foot ulcers and further nerve damage can be prevented with circulatory treatment and acupressure therapy that can maintain blood circulation to the extremities. The purpose of this case study is to describe the application of acupressure and circulatory care combination to diabetic patients with spleen dampness syndrome. This case study was conducted over three visits in three weeks, using the method of applying foot care, foot exercises, foot spa and footwear selection combined with acupressure techniques on certain meridians to 2 diabetic patients. The results achieved were in the form of decreased complaints of tingling, numbness, and pale skin tone, increased peripheral pulse strength, and improved filling of capillaries and skin turgor. This shows that acupressure-circulation treatment combination was able to reduce neuropathy score from low-risk category to very low-risk category. The case study showed that the application of acupressure-circulation combination was successful in improving peripheral perfusion. Future research was recommended to measure circulation using the Ankle-Brachial Index (ABI) and doppler methods to get an accurate evaluation.